Performance of real time traffic in the ethernet and wlan using tcp and udp protocols - Punitha, Subbramaniam (Universiti Malaysia Sarawak (UNIMAS), 2010)
The WLAN industry has emerged as one of the fastest-growing segments of the communication trade. This project is aimed towards evaluating the real-time traffic performance in Wireless LAN (WLAN) and Ethernet using TCP and UDP protocol. Analysis is done to acknowledge the advantages and disadvantages of both protocols. Two different types of traffic are considered namely, voice and video. The evaluation was done using ns-2 simulator (version 2.34) running on Ubuntu. The metrics used in the evaluation are throughput (byte), delay (sec) and packet loss (%). Depending on graphs of these three metrics, the performance of TCP and UDP are evaluated, requirements are determined. Through this simulation study, a summary is made saying that the UDP protocol performs better and be accessed at a faster speed for different traffic types. Simulation results show that UDP performs better performance than legacy TCP. Depending on ITU-T requirements especially for delay and packet loss, the acceptable number of streams both for traffic type individually and with comparisonwith the TCP voice and video metrics of traffics can be determined under UDP protocol.